CALENDAR ANOMALIES OF JANUARY EFFECT, DAY OF THE WEEK EFFECT AND SIZE EFFECT TOWARD STOCK RETURN ON GO PUBLIC COMPANY LISTED INDONESIA STOCK EXCHANGE PERIOD 2013 – 2017 - Aprilia, Nanda B1024141010 (Jurnal Manajemen Update, 2019)
An efficient capital market hypothesis says that markets that efficiently react quickly to relevant information. In an efficient market, the market will quickly react to new information coming in so that a new equilibrium price will be reached quickly. In practice in the capital market phenomena appear that show deviations that are contrary to the concept of efficient capital markets (market anomaly). The pupose of this research to investors because Investors need information to assess the risks involved in their investments and to estimate returns on the investment. With the information obtained, investors can determine the position of selling, buying or holding a stock. These anomalies including the January Effect, Day of The Week Effect and Size Effect. The data used in this study are secondary data from companies listed on the Indonesia Stock Exchange during the study period from January 2013 to December 2017. The samples used in this study were 55 issuers with purposive sampling method. The statistical analysis used in this study is by multiple regression analysis with dummy variables for January effects and Day of The Week effect while different T tests for firm size effects. The results of hypothesis testing with multiple linear regression analysis with Independent variables, namely January Efeect, Day Of The Week Effect, and Size Effect and Dependent variables namely Stock Return. Based on the results of multiple linear regression test analysis using dummy variables showing that the January Effect of each variable has a significant influence on Stock return and on the day of the week effect on Monday, Tuesday, Wednesday, Thursday and Friday also has a significant effect on stock returns. While the size effet based on the results of the independent t-test on the size effect variable of a company has a significant effect (<0.05) which means that the size of a company has an impact on a company's stock return, where the company is measured based on total asset.